Eradication of Multidrug‐Resistant Staphylococcal Infections by Light‐Activatable Micellar Nanocarriers in a Murine Model. (29th September 2017) - Liu, Yong; van der Mei, Henny C.; Zhao, Bingran; Zhai, Yan; Cheng, Tangjian; Li, Yuanfeng; Zhang, Zhenkun; Busscher, Henk J.; Ren, Yijin; Shi, Linqi
Abstract: Bacterial infections are mostly due to bacteria in their biofilm mode‐of‐growth, making them recalcitrant to antibiotic penetration. In addition, the number of bacterial strains intrinsically resistant to available antibiotics is alarmingly growing. This study reports that micellar nanocarriers with a poly(ethylene glycol) shell fully penetrate staphylococcal biofilms due to their biological invisibility. However, when the shell is complemented with poly(β‐amino ester), these mixed‐shell micelles become positively charged in the low pH environment of a biofilm, allowing not only their penetration but also their accumulation in biofilms without being washed out, as do single‐shell micelles lacking the pH‐adaptive feature. Accordingly, bacterial killing of multidrug resistant staphylococcal biofilms exposed to protoporphyrin IX‐loaded mixed‐shell micelles and after light‐activation is superior compared with single‐shell micelles. Subcutaneous infections in mice, induced with vancomycin‐resistant, bioluminescent staphylococci can be eradicated by daily injection of photoactivatable protoporphyrin IX‐loaded, mixed‐shell micelles in the bloodstream and light‐activation at the infected site. Micelles, which are not degraded by bacterial enzymes in the biofilm, are degraded in the liver and spleen and cleared from the body through the kidneys. Thus, adaptive micellar nanocarriers loaded with light‐activatable antimicrobials constitute a much‐needed alternative to current antibiotic therapies. Abstract : Photodynamic treatment with protoporphyrin IX‐loaded micelles is successful in eradicating a subcutaneous, multidrug‐resistant infection in mice, while unused micelles are demonstrated to be cleared from the blood circuation.